Anomalous bidding in short-term treasury bill auctions - Michael J. Fleming; Kenneth D. Garbade; Frank Keane (Federal Reserve Bank of New York, 2004)
We show that Treasury bill auction procedures create classes of price-equivalent discount rates for bills with fewer than seventy-two days to maturity. We argue that it is inefficient for market participants to bid at a discount rate that is not the minimum rate in its class. The inefficiency of bidding at a rate other than the minimum is related to a quantity shortfall rather than an unexploited profit opportunity. Auction results for weekly offerings of four-week bills and occasional offerings of cash management bills show that market participants frequently bid at inefficient rates. However, they are more likely to bid at efficient rates than chance would suggest.
Keywords: G14; H63; 330; Schatzpapier; Auktion